Os desafios para o acesso da população analfabeta funcional aos serviços públicos eleitorais - Hermont, Rodrigo Calumby (2023)
The Electoral Justice has highly capillarized bodies, which provide services to a myriad of citizens throughout Brazil. In this context, there is a significant number of voters who do not have or have a low level of education and find it difficult to learn about their rights and use public electoral services. Added to this panorama is the rapid evolution of technologies, often not absorbed by this portion of the population. Thus, there is a problem-situation to be faced: how to bring citizens closer to public electoral services in a simplified and clear way, providing a quality public service and respecting socio-educational peculiarities and limitations? Given the above, this study aims to diagnose the best means to disseminate, expand and democratize the effective use of the public service by the illiterate and low-education population. The theoretical support covers the bibliographical research of the main researchers in the communicational and administrative areas, in line with the current legislation on the subject. The dissertation project is classified in terms of approaching the problem as qualitative and quantitative, when analyzing age and education data provided by the Superior Electoral Court (TSE) together with qualitative data, provided by the reports of the ombudsman of the Regional Electoral Court of Espírito Santo ( TRE-ES). As for the method, the research is descriptive and correlational, as it intends to demonstrate the relationship between the demographic profile of the electorate and the type of demand for the electoral services offered. The survey sample is made up of voters from the state of Espírito Santo whose vote is mandatory (18 to 70 years old). The technical-technological product (PTT) consists in the elaboration of a visual piece to present the voter registration transfer procedure in a simple language and with the graphic aid of visual law techniques.